Tafsir Inklusif Quraish Shihab: Kajian atas Penggunaan Sumber-Sumber Syiah dalam Menafsirkan Al-Qur’an - Affandi, Abdullah; Billah, M. Mu'tashim (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2024)
This research examines the inclusive tafsir approach employed by Quraish Shihab in his work, Tafsir Al-Mishbah, particularly regarding the use of Shia sources. As one of Indonesia's leading mufassirs, Quraish Shihab offers a moderate and dialogical interpretive perspective aimed at bridging sectarian differences. This study seeks to analyze how Quraish Shihab cites, integrates, and responds to the views of Shia scholars, particularly in interpreting verses related to Ahlul Bayt. The research employs a qualitative method with a literature study approach, focusing on Tafsir Al-Mishbah and other supporting sources. The findings reveal that Shihab's inclusive methodology not only enriches the understanding of Quranic texts but also contributes to inter-sectarian dialogue and tolerance in a modern context marked by religious polarization. By integrating diverse viewpoints, Shihab offers a model for interpretation that promotes harmony among various Islamic traditions, ultimately fostering peace and mutual respect within the broader Muslim community. This research highlights the significance of Shihab's approach in addressing contemporary challenges of pluralism and religious diversity in Indonesia and beyond.